HIGH SCHOOL STUDENTS PROFILE OF MISCONCEPTION IN ROTATIONAL DYNAMICS - WAHYU KURNIAWAN, YONDA; JATMIKO, BUDI (Inovasi Pendidikan Fisika, 2019)
Abstract This research aims to describe student?s profile of misconception on rotational dynamics before and after remidial instructions using beach ball discussion learning model. This research used pre-experimental design with one-group pre-test post-test design. Subjext of this research is 21 science class student in Lamongan, Indonesia. Before the instruction conduct, three-tier diagnostic test formatted pre-test is given to reveal student misconceptions profile. Physic instructions using beach ball discussion learning model then conducted. After the instructions, the same diagnostic test formatted was given as post-test. Collected data then analyzed to describe student misconceptions profile before and after the instructions. The result show that before the instructional there are misconception students got as average in every concept, after the instructions, misconceptions was reduced. Keywords : Misconception, Remidial, Rotational Dynamics Abstrak Penelitian ini bertujuan untuk mendeskripsikan profil miskonsepsi siswa pada materi dinamika rotasi sebelum dan sesudah pembelajaran remidial dengan model diskusi tipe beach ball. Jenis penelitian yang digunakan adalah pre-experimental design dengan rancangan one-group pre-test post-test design. Subjek penelitian adalah 21 siswa kelas XI MIA di Lamongan, Indonesia. Sebelum dilakukan pembelajaran, siswa diberi pre-test berupa tes diagnostik miskonsepsi bertipe three-tier untuk mengetahui profil konsepsi awal siswa. Setelah dilakukan pre-test, pembelajaran remidial dengan model diskusi tipe beach ball dilaksanakan. Setelah pembelajaran dilaksanakan, siswa diberi post-test berupa tes diagnostik yang sama dengan pre-test. Data yang terkumpul dianalisis untuk mendeskripsikan profil konsepsi siswa sebelum dan sesudah pembelajaran. Hasil penelitian menunjukkan bahwa sebelum pembelajaran remidial secara rata-rata siswa mengalami miskonsepsi di setiap konsep dan setelah pembelajaran dilaksanakan jumlah miskonsepsi yang dialami siswa berkurang. Keywords: Miskonsepsi, Remidial, Dinamika Rotasi